Avaliação da fermentação alcoólica extrativa em diferentes temperaturas com remoção de etanol por arraste com CO2 - Veloso, Ivan Ilich Kerbauy (Universidade Federal de São Carlos, 2023)
By reducing the fermentation temperature, the inhibitory effect of ethanol is also reduced, resulting in wines with higher ethanol contents, but with a significant decrease in ethanol productivity, due to the negative effect of temperature on fermentation kinetics. Another option for overcoming product inhibition is to remove part of the ethanol from the fermentation broth as it is produced, using CO2 stripping, which increases ethanol productivity and allows the feeding of more concentrated musts. Combining the two process strategies, the present work evaluated extractive fed-batch ethanol fermentation with the removal of ethanol by CO2 at temperatures of 28, 30, 32, and 34 °C. Firstly, a study was carried out to determine the influence of temperature on ethanol fermentation, using monitoring by mid-infrared spectroscopy (FT-MIR). Next, a mass balance of fed-batch ethanol fermentation with high cell density (HCD) was performed, considering the volume of cells (intrinsic modeling). Using a mixed kinetic model of cell growth, considering the inhibitions by substrate, product, and cells, evaluation was made of the effects of different cell concentrations on the kinetics of ethanol fermentation at different temperatures and with high substrate concentration in the must (VHG). Subsequently, a thermal analysis of the extractive fermentation was conducted at different temperatures, using simulations to find the gas flow rate that resulted in the best saving of water used for temperature control. Finally, extractive fermentation at different temperatures was optimized in terms of ethanol productivity. The monitoring of ethanol fermentation by FT-MIR showed excellent performance since it minimized the interference of temperature in the spectral bands when using calibration models with spectra acquired at different temperatures. The FT-MIR technique was essential for decision-making in extractive fermentations, including determination of the exact moment to start stripping, and productivity calculations. The developed intrinsic modeling improved substrate prediction, especially under VHG conditions. Fermentations at different cell concentrations were modeled and the parameter that reflected cell inhibition was correlated with the cell concentration in the inoculum and with temperature. The experimental validation of the optimal condition for water reduction by temperature control resulted in 61.9% water saving and a total ethanol content of 15.2 °GL for HCD and VHG extractive fermentation at 28 °C. Regarding the optimization of the process in terms of ethanol production, the extractive fermentation at 28 °C resulted in 142.1 g L-1 (18 °GL) of ethanol and high volumetric ethanol productivity of 9.6 g L-1 h-1. Furthermore, a high concentration of ethanol in the wine (14 °GL) was obtained, since less ethanol was removed by CO2 at lower temperatures. Therefore, the strategy of using stripping in ethanol fermentations at low temperatures proved to be promising, resulting in high ethanol productivity and providing environmental and economic advantages including water savings and other benefits from obtaining wines with high ethanol content, such as reduction of steam in distillation, reduction in the volume of vinasse generated, and other savings for inputs such as antibiotics and sulfuric acid related to bacterial contamination, contributing to cost reduction in the ethanol production process.
Evaluation of extractive ethanol fermentation at different temperatures with ethanol removal by CO2 stripping
Keywords: Fermentação alcoólica; Baixa temperatura; Batelada alimentada; Fermentação extrativa; Arraste gasoso; Modelagem; VHG; HCD; Ethanol fermentation; Low temperature; Fed-batch; Extractive fermentation; Gas stripping; Modeling; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA